Analytical progresses of the International Olympic Committee and World Anti-Doping Agency Olympic laboratories. (July 2012) - Georgakopoulos, Costas; Saugy, Martial; Giraud, Sylvain; Robinson, Neil; Alsayrafi, Mohammed
The Summer Olympic Games constitute the biggest concentration of human sports and activities in a particular place and time since 776 BCE, when the written history of the Olympic Games in Olympia began. Summer and Winter Olympic anti-doping laboratories, accredited by the International Olympic Committee in the past and the World Anti-Doping Agency in the present times, acquire worldwide interest to apply all new analytical advancements in the fight against doping in sports, hoping that this major human event will not become dirty by association with this negative phenomenon. This article summarizes the new analytical progresses, technologies and knowledge used by the Olympic laboratories, which for the vast majority of them are, eventually, incorporated into routine anti-doping analysis.